Strategi Pembelajaran Pendidikan Agama Islam di Era Society 5.0 - Ihya' Ulumuddin (Kariman: Jurnal Pendidikan Keislaman, 2023)
The wave of the Society 5.0 era was marked by massive efforts and human labor which were replaced by robots connected to computers. Seeing this fact, PAI (Islamic Religious Education) must make efforts to adjust its best strategy in implementing learning. So, in such conditions the use of technology is a necessity as a response in order to overcome the gaps or problems that exist in PAI learning so that it can be carried out more meaningfully and in harmony in response to the development of Era Society 5.0. This study uses a literature study method with a descriptive qualitative approach, and data collection techniques through various relevant articles and books. Using hermeneutic analysis so as to be able to capture the meaning, values ​​and intent of the PAI learning strategy in the Society 5.0 era, and finally the conclusion. The results of the study show the steps of the PAI learning strategy in the Society 5.0 era, including: 1) Encouraging students to study Islamic religious education with full discipline and earnestness. 2) Think critically. 3) Futuristic PAI learning orientation. 4) Selection of the right learning model. 5) Integrate facilities and infrastructure as well as learning resources based on information and technology.